Winners'chapel (Nigeria and Ghana): governance and fund management (2007)
This study sought to identify and evaluate the various aspects and forms of ' religious economy', the governance superstructure within which such economy operates and the consequences for the church and society in Nigeria and Ghana with specific reference to Winners' International Chapel, its splinter group in Ghana as well as what remains of the original Winners' Chapel in Ghana. Specifically, the study investigated the logic of 'giving', problems associated with soliciting, giving and managing church economic resources, the analysis of gainers and losers and effects on individual and group attitudes. Through the analysis of church records, in-depth interviews of church leaders and focus group discussions with section of the laity, the study investigateds some branches of Winners' chapel in Nigeria and the two variants in Ghana. It examined sole and corporate patterns of church governance; and the pattern of domestic and international flow and management of church resources. The selected Nigerian church has programme extensions to Ghana and other African countries.Field study, therefore, covered Nigeria and Ghana. Data analysis was guided by the politicl economy of the church. The study was executed within some 12 months by this researcher with assistance from those knowledgeable within the setting of this church. It was discovered that though the governance is dictated by the founder, the membership did not mind it. Rather they believed giving generously to the work of the Lord was in turn bringing blessings upon them. They were also happy with the fact that they could see what thier monies were spent on- physical structures especially.